2016
DOI: 10.1155/2016/6427681
|View full text |Cite
|
Sign up to set email alerts
|

In VitroCytokine Expression andIn VivoHealing and Inflammatory Response to a Collagen-Coated Synthetic Bone Filler

Abstract: The goal of the present work was to investigate the relationship between in vivo healing and inflammatory response and in vitro cytokine expression by macrophages of a synthetic bone filler (25% hydroxylapatite-75% β-tricalcium phosphate) bearing a surface nanolayer of collagen. A clinically accepted, state-of-the-art xenograft material was used as a “negative control,” that is, as a material that provides the correct clinical response for the intended use. In vitro data show that both materials exert a very l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…From Brånemark's initial studies, titanium represents the most-used material, although not the only one, for the production of endosseous dental implants [1][2][3]. Success rates with titanium implants are high in both the short and long term; moreover, they are indicated in many particular situations [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…From Brånemark's initial studies, titanium represents the most-used material, although not the only one, for the production of endosseous dental implants [1][2][3]. Success rates with titanium implants are high in both the short and long term; moreover, they are indicated in many particular situations [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a human experimental study, results indicated that a significantly greater proportion of oral mucosa came into contact with the nanoporous TiO 2 surface than that with the unmodified surfaces [92]. This technique is also used to coat bone substitutes with a nanolayer of osteoconductive material [93].…”
Section: Sol-gel Coatingmentioning
confidence: 97%
“…Nowadays, the demand for new and more efficient and performing materials to be applied in the dental field is growing [3] , [4] , [5] , [6] , [7] . The latest trends indicate that the use of a hybrid material, consisting of a scaffold and a biological component, is the future of dental bone tissue engineering [8] .…”
Section: Introductionmentioning
confidence: 99%